Intrinsic normalizations of a nonholonomic hypersurface with m-dimensional generators in affine space An - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2002)
In this article intrinsic normalizations of a nonholonomic hypersurface with m-dimensional generators in affine space An is constructed in an invariant form.